Evaluating the corrosion protection of post-tensioning grouts : standardization of an accelerated corrosion test - Pacheco, Alexandre Rodrigues (2003)
Post-tensioning grouts, typically a mixture of cement and water (sand, mineral chemical admixtures can also be used), are not only designed to transfer stresses between cables and precast concrete, but also to protect prestressing strands against corrosive phenomena. A recent concern regarding post-tensioned structures is the possibility that corrosive agents may reach grouted steel tendons and start a sequence of events culminating in catastrophic collapse. This possible scenario motivated the creation of the Accelerated Corrosion Test (ACT) intended to measure the degree of corrosion protection for grouts used in post-tensioning applications. This test is currently recommended by the Post-Tensioning Institute (PTI). Although already in use, the ACT is not fully developed and researchers have been pointing out the need for further studies to evaluate the influence of the IR drop effect on ACTs (a loss in the applied potential due to the resistivity of corrosion cells) because this phenomenon is likely to skew results for grouts of significant different resistivity. Five different categories of grout (plain, prepackaged, with corrosion inhibitors, with silica fume, and with fly ash) were tested in an electrochemical setup capable of compensating for IR drop effects. Procedures are recommended for adoption in an improved version of the ACT standard.